Performance analysis of dye-sensitized solar cells with various MgO-ZnO mixed photoanodes prepared by wet powder mixing and grinding. Issue 21 (15th December 2021) - Chen, Huai-Yi; Koo, Horng-Show; Hsu, Yung-Lin; Lu, Chun-Hung
Abstract : In this study, photoanodes of a dye-sensitized solar cell (DSSC) were made by adding various weight percentages (0∼9 wt%) of MgO nanopowder to ZnO nanopowder with a different wet powder mixing and grinding method. For the MgO/ZnO DSSCs, the addition of 1 wt% MgO can achieve maximum short-circuit current density (4.00 mA/cm 2 ) and maximum photovoltaic conversion efficiency (1.03%), which was 39% and 27% better than those of the reference ZnO DSSCs, respectively. When a small amount of MgO was added, the electron transport rate or the efficiency of electron injection into photoanodes was improved. However, when a large amount of MgO was added, the number of carriers generated by light was lowered, which led to performance degradation in DSSCs. Preparing photoanodes by adding a small amount of MgO to ZnO can thus effectively improve the photovoltaic performance of ZnO DSSCs.